A review on regulation of DNA methylation during post-myocardial infarction - Han, Wenqiang; Wang, Wenxin; Wang, Qinhong; Maduray, Kellina; Hao, Li; Zhong, Jingquan (Frontiers in Pharmacology, 2024)
Myocardial infarction (MI) imposes a huge medical and economic burden on society, and cardiac repair after MI involves a complex series of processes. Understanding the key mechanisms (such as apoptosis, autophagy, inflammation and fibrosis) will facilitate further drug development and patient treatment. Presently, a substantial body of evidence suggests that the regulation of epigenetic processes contributes to cardiac repair following MI, with DNA methylation being among the notable epigenetic factors involved. This article will review the research on the mechanism of DNA methylation regulation after MI to provide some insights for future research and development of related drugs.